GEOSLICIER AND ITS APPLICATION FOR SOIL STRATA ANALYSIS - T. Harianto; T. Hino; R. Jia; K. Ohgushi; T. Ichihara (Lowland Technology International, 2013)
Many "nogoshi" i.e, lower sections of the river bank that allow upstream floodwater overflow, have been built on the Jobaru River in Kyushu Island, Japan. The soil strata in the floodpain adjacent to the Yago Nogoshi of the Jobaru River were studied using a Geoslicier. The sedimentary facies and the sedimentary ages of the soil strata were determined using Geoslicier samples. The sedimentary environmental of the test site was defined, and soil strata formed by sediments during large floods were identified. The layers below ground level (G.L.) -1.50 to -1.70 m are river channel deposits, and the layers above G.L. -1.50 to -1.70 m are back marsh deposits. The result of radiocarbon dating show that the river channel deposits were formed before AD 1500. The lower layers of the back marsh deposits, which contain a considerable quantity of plan roots, were formed at approximately AD 1600. The upper layers of the back marsh deposits, which contain a small quantity of plant roots, were formed after AD 1600. The time of artificial land alterations was deduced based on the results of the sample analyses.